Model Dinamik Pengelolaan Limbah Minyak Goreng Bekas di Kota Denpasar - wahyuni, deria; Satriawan, I Ketut; Sandyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 3 (2022): SeptemberDO - 10.24843/JRMA.2022.v10.i03.p06, 2022)
Waste cooking oil ( WCO ) is oil that has been used for frying more than three times, so it is classified as dangerous which can endanger human health and also have a negative impact on the environment. The city of Denpasar every month produces approximately 604,629 liters/month of waste cooking oil until now it has not been clearly managed. WCO if managed properly will be a potential, because it can be processed into products and provide added economic value. The purposes of this research were to analyze the potential of WCO management in Denpasar City and develop a design model for WCO management in Denpasar City. This research was conducted using a dynamic system approach, and system simulations were carried out from 2020 to 2030. The development of a dynamic model of WCO utilizes secondary and primary data. The simulation results show the factors that influence the behavior of the model, namely the supply of household WCO, the supply of non-household WCO and waste treatment technology. The simulation results on existing conditions in 2030 show that the stock of waste cooking oil cannot meet the demand for waste cooking oil. Based on the simulation results of several scenarios, alternative policy recommendations that are in accordance with the objectives are scenario 4 (combined scenarios) which can produce a supply of used cooking oil of 229,897.75 liters in 2025 and increases to 253,348.94 liters in 2030.